Analisis Psikologi Humanistik Tokoh Utama Novel Maysuri Karya Nadjib Kartapati Z - Azren, Azmira (Edusia: Jurnal Ilmiah Pendidikan Asia, 2022)
The problem in this study is how the humanistic psychology consisting of five aspects of multilevel needs in the main character of the novel Maysuri by Nadjib Kartapati Z. The purpose of this study is to explain the needs of the main character in the novel Maysuri by Nadjib Kartapati Z using Abraham Maslow's theory of humanistic psychology. The method used is descriptive qualitative research method that describes data in the form of observations on the multi-level needs of Maysuri's character. The data collection technique used is reading and note taking. The data analysis technique used is grouping the data, interpreting the data, presenting the analysis description, and concluding the research results. Based on the results of the study, it is known that the humanistic psychological needs of the main character, Maysuri, have been well met, which are as follows 1) Physiological needs, consisting of satisfying the needs for food and water, air, clothing, rest and shelter. 2) Safety needs, consisting of physical safety and psychological safety. 3) Love and affiliation needs, which consist of family affection, partner affection, and community acceptance. 4) Self-esteem needs consist of self-esteem and esteem from others. 5) Self-actualization needs in the form of realizing one's potential as a teacher and family helper.